Study of the immunotoxic properties of pegylated hyaluronidase - K. I. Ershov; A. M. Shvetsova; E. Yu. Sherstoboev; A. A. Churin; V. V. Zhdanov; M. A. Korolev; P. G. Madonov (Сибирский научный медицинский журнал, 2023)
The development of safe drugs occupies a special place in the pharmaceutical industry. One of the main tasks of its preclinical phase is to evaluate possible toxic effects of the developed drug on the body and on various systems, including the immune system. The aim of our work was to study immunotoxic properties of pegylated hyaluronidase (PEG- HYAL). Material and methods. Mice F1(CBA/C57Bl/6) were divided into subgroups which were intragastric and intraperitoneally administered with PEG-HYAL in different dosages (50, 500, 1250, 2500 and 5000 U/kg). The number of antibody-producing cells in the spleen, the mass and cellularity of central and peripheral immune organs, phagocytic activity of peritoneal macrophages and neutrophils, delayed hypersensitivity reaction (DHR), level of hemagglutinin to sheep erythrocytes, spontaneous and mitogen-induced splenocyte proliferation were determined. Results. PEG-HYAL did not induce DHR, did not suppress phagocyte activity of peritoneal macrophages, at a dose of 50 ED/kg did not significantly affect the hemagglutinin content to erythrocytes, but at a dose of 500 ED/kg did statistically significantly reduce the titer of specific antibodies. When experimental animals were exposed to PEG-HYAL at doses of 50 and 500 U/kg, spontaneous and mitogen-induced proliferation of splenocytes decreased. Conclusions. The PEG-HYAL trial produced results that can be used to substantiate the administration of the PEG-HYAL-based medication.